Transsexualism illusion and reality - Chiland, Colette (Disseminations., 2003)
Transsexualism is a stimulating, proactive and important book. Colette Chiland does not back away from difficult issues. She forces all of us to look at our assumptions about t5ranssexualism and to re-examine what gender and sex really mean' - Christine Ware, author of Where Id Was: Challenging Normalization in Psychoanalysis 'In a nutshell, the book offers a much-needed alternative view of transsexuality from a psychiatric and European point of view... Chiland's interesting and well presented book is a valued reminder of how different the same topic can appear in an alternative perspective' - Transgender Tapestry Colette Chiland exhibits a masterful and encyclopedic knowledge of transsexualism, drawing together the insights of depth psychology, psychoanalysis, history, anthropology and sociology for rethinking transsexualism in terms of identity, subjectivity and the wider socio-historical world. This book is written with considerable precision on complex, technical issues, whilst at the same time keeping the broader question of the relationship between transsexualism and society firmly in mind.